Catalytic Organic Synthesis: An Eco-Friendly Approach - Srivastava, Tanuja (Asian Journal of Chemistry, 2010)
Ni/Kieselguhr represents an important class of catalysts that offer an attractive alternative to the conventional Friedel-Crafts catalyst used for alkylation, which are corrosive and environmentally hostile. Exchanged Ni/kieselguhr catalyst is extensively used for alkylation, isomerization and molecular transformation. The techniques of electron microscopy and X-ray diffraction are used for obtaining information regarding the microstructure and interplanar spacing in the catalyst. Study of kinetics of reaction in the presence of catalyst provides parameters needed for reactor design.